Implementation Of Digital Marketing For Msmes Pentol Mercon 88 In Batam City - Putri Siti Rohaizat; Golan Hasan (ConCEPt - Conference on Community Engagement Project, 2023)
Digital marketing has become the most preferred marketing strategy and has been widely practiced by business actors since the Covid-19 pandemic. This is the result of the adaptation of business actors to changes in consumer behavior since the pandemic. Even so, Pentol Mercon 88 as a business engaged in the culinary field, has yet to adapt to this fully and is more fixated on conventional promotional techniques. This project aims to help businesses implement digital marketing to expand market reach and compete with similar businesses. Qualitative research was conducted using the observation method at business locations and interviews with the owner of Pentol Mercon 88. The result of implementing this digital marketing strategy is increasing brand awareness and reaching a broader market which is marked by increasing the number of followers and engagement on business social media accounts, as well as increasing business income.